Volumetric histological characterization of optic nerve degeneration using tissue clearing: literature review and practical study. (2nd October 2021) - Myers, April; Ford, Jonathan; Decker, Summer; Crawford, Fiona; Tzekov, Radouil
ABSTRACT: Tissue clearing technologies can greatly improve the depth and accuracy with which the three-dimensional structure of tissues, especially those of th*-e nervous system, can be visualized. A review of the present literature suggests that the growing diversity and sophistication of various approaches have contributed to the expansion of this method to a greater variety of tissue types, experimental conditions, and imaging modalities. In the proof-of-concept study presented in this paper, a simplified and modified version of the tissue clearing method CUBIC (clear, unobstructed brain imaging cocktails and computational analysis) was used in conjunction with fluorescent staining and immunohistochemistry to illustrate the three-dimensional structure and molecular characteristics of inflammatory and degenerative activity in the mouse optic nerve. Based on the studies summarized in this mini-review, and our impression from using the mCUBIC method, it appears that tissue clearing could be a viable approach revealing three-dimensional histological features of myelin-rich tissues under normal conditions and after injury.